(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2025)
Previous research has provided compelling accounts of how the alter-globalization movement develops alternative visions of globalization that are firmly rooted in local struggles and place-based politics, celebrating cultural distinctions and local idiosyncrasies, while at the same time embracing global movement building and place-based globalism and expressing both local and cosmopolitan identities and values. Given these findings of previous research, how do alter-globalization movement participants think about place identity, place meaning, and place attachment? What is their sense of place? We explore these questions in the context of the Slow Food movement, a global network that brings together many locally-oriented activists to transform the food system. Our semi-structured interviews with Slow Food movement participants provide evidence and examples that are indicative of the presence of place-based politics and place-based globalism in the Slow Food movement. This research contributes to the literature in two ways: It synthesizes and applies place-based concepts to the study of highly diverse transnational movement spaces to generate a deeper understanding of transnational social movement participants’ sense of place and of the solidarities and shared identities that they develop, and it highlights the voices and personal stories transnational food movement participants shared during interviews as they reflected on issues of place.